Analysis of Character Values in the Rambu Solo' Traditional Ceremony for Early Childhood - Idamawati Makkatang; Yeni Rachmawati; Euis Kurniati (Early Childhood Education & Parenting, 2025)
Character education aims to build a strong nation where people have noble morals, are moral and tolerant, and work together. Therefore, character education in early childhood is considered important because at an early age children's character is easy to shape because children imitate and absorb behavior from the surrounding environment more quickly. The effort in passing on culture to early childhood in Tana Toraja Regency involves early childhood in cultural activities. One of the activities involving early childhood is the Rambu solo traditional ceremony. The purpose of this study was to determine the character education values reflected in the Rambu solo' traditional ceremony for early childhood and to determine the involvement of early childhood in the Rambu solo' traditional ceremony. The research method used is an ethnographic method with a qualitative approach. The data collection techniques are observation, interview, and documentation. The results of this study are the value of character education that exists in the Rambu solo' ceremony for early childhood is religious, social care, tolerance, discipline, and curiosity. Furthermore, the form of early childhood involvement in the Rambu solo' ceremony is to receive guests tailored to their physical abilities.